영어 듣기이해에 ‘소리내어 읽기전략’이 주는 영향에 대한 연구 - 신규철(Shin Kyu-Cheol) (영미연구, 2017)
본 연구는 외국어교육 상황에서 영어 읽기교육의 효과적인 전략으로서 ‘소리내어 읽기전략’을 논의하고, 그 전략의 인지적 측면을 분석하며, 소리내 읽기가 듣기 이해도에는 어떠한 영향을 주는지를 밝히는데 그 목적이 있다. 소리내 읽기 전략은 문자언어를 음성언어로 전환하여 읽기를 할 때 나타나는 인지적 발달과 이해력 향상을 증명하고 있다. 소리내 읽기는 의미단위 끊어 읽기, 연음, 억양과 톤의 변화, 영어 자음과 모음의 음소인식을 이해하고 훈련함으로써, 외국어 학습에서 목표언어를 효과적으로 이해하는 중요한 전략이 되고 있다. 또한, 본 논문에서는 실험을 통해 전통적인 묵독 집단과 소리내 읽기 집단의 듣기 이해도를 비교 분석하고, 소리내 읽기집단의 듣기 수행과정에 대한 질적 평가를 통해, 목표언어의 음성학적인 부분의 학습효과를 논의한다. 그리고 영어학습에서 소리내 읽기가 듣기이해에 미치는 영향을 알아보기 위해, 통제집단과 실험집단을 각각 사전평가와 사후평가로 나누어 실험한 결과, 소리내 읽기 집단이 묵독 집단에 비해 상대적으로 큰 향상을 보인다. This study aims to investigate reading-aloud strategy and look into its effects on listening comprehension in EFL context. Reading and listening are the skills in the comprehension category, while writing and speaking in the production category of the language four skills. In this regard, reading can be a significant tool to improve listening competence. As an alternative method of reading strategy, reading aloud plays a crucial role in comprehending texts from cognitive and affective point of view. This study discusses various aspects of reading-aloud strategy and then its benefits. And in the experimental study, twenty Korean college students were divided into two groups: The one is the control group involved in the silent reading method and the other is the experiment group administered in the reading-aloud strategy. Each group was taught English reading materials for four months and after the reading instruction, the listening comprehension questions were given to students. Compared with the pre-test in the listening comprehension, the results of post-test were superior to those of pre-test from a phonetic point of view. In addition, the qualitative research about the phonemic awareness for the listening comprehension are carried out. And this study analyzes the listening process through the reading-aloud strategy and its benefits as well. KCI Citation Count: 2